Analisis pemasaran sosial di SMPN 98 Jakarta - Widyoseno, Ary; Ilma, Hafizha; Zuliansyah, Zulfi; Bikriya, Dara; Rahmah, Dizza Nur; Larasati, Dyah Ayu; Ristiana, Fita; Mandasari, Helena; Ramadhan, Javas Rizqi; R, M. Akbar Ridho; Tazkiya, Nadja; Farrasati, Rheina Audy (Journal of Youth and Outdoor Activities, 2024)
Background: Smoking is a serious problem that must be addressed immediately. SMPN 98 Jakarta has clear regulations in an effort to deal with smoking behavior in the school area, however, there is still a lot of smoking behavior among students. Methods: This research was conducted through a qualitative field model by applying several stages of social intervention. Findings: The process of implementing target marketing at SMPN 98 Jakarta researchers used objective communication targets and strategic communication. Conclusion: The results of this study found several facts. First, related to the students' hanging out habits. Second, there are external parties who often smoke in the school area such as security guards, snack sellers, motorcycle taxi drivers, and local residents. In addition, there are cigarette sellers that are easily found in the neighborhood around the school.